Case of Squamous Cell Carcinoma Transformation in Ovarian Mature Cystic Teratoma: A Case Report - Chandra, Pratibha; Kinra, Prateek; Bhandoria, Geetu; Malik, Ajay (Annals of Pathology and Laboratory Medicine, 2019)
Mature cystic teratoma (MCT) is the commonest benign tumour arising in an ovary. Malignant transformation in a MCT of ovary is exceptionallyrare, seen only in1-2% cases.The most common malignant transformation in a benign teratoma of ovary is squamous cell carcinoma. The other malignant transformations in teratoma include adenocarcinoma, melanoma and basal cell carcinoma. The patients having this malignant transformation in teratoma have a very low 5-year survival rate of 20% approximately. Here; we describe a case of advanced-stage squamous cell carcinoma arising in a mature cystic teratoma in a 34-year-old woman.This solid high grade malignancy was missed in the pre-operative imaging which showed a right adnexal mass with echogenic foci within and septations, and was reported as a dermoid cyst. The intraoperative frozen section too taken from the thin portion of the cyst wall was reported as cystic teratoma. However in the staging laparotomy,right salpingo-oophorectomy and left oophorectomy, specimen the patient was reported to have moderately differentiated squamous cell carcinoma arising in a benign mature cystic teratomawith extensive tumour necrosis with omental tumour deposits.In view of initial incomplete surgery and advanced stage, decision of completion cytoreductive surgery was taken. The patients with mature cystic teratoma with high age (post-menopausal), a size of more than 10 cm and increased serum tumour markers should be suspected to have a malignant transformation and should be investigated thoroughly.